2015
DOI: 10.1098/rsbl.2014.0850
|View full text |Cite
|
Sign up to set email alerts
|

Partial migration: growth varies between resident and migratory fish

Abstract: Partial migration occurs in many taxa and ecosystems and may confer survival benefits. Here, we use otolith chemistry data to determine whether fish from a large estuarine system were resident or migratory, and then examine whether contingents display differences in modelled growth based on changes in width of otolith growth increments. Sixty-three per cent of fish were resident based on Ba : Ca of otoliths, with the remainder categorized as migratory, with both contingents distributed across most age/size cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 19 publications
(27 reference statements)
3
58
0
Order By: Relevance
“…Furthermore, an otolith chemistry study on black bream demonstrated the presence of partial migration (i.e. populations consist of both resident and migratory individuals) within the Murray River estuary, with each migratory contingent having different growth histories (Gillanders et al 2015). Although, the presence of partial migration has not been investigated in Tasmanian populations, this suggests that South Australian populations may be exposed to a broader range of environmental conditions throughout their life cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, an otolith chemistry study on black bream demonstrated the presence of partial migration (i.e. populations consist of both resident and migratory individuals) within the Murray River estuary, with each migratory contingent having different growth histories (Gillanders et al 2015). Although, the presence of partial migration has not been investigated in Tasmanian populations, this suggests that South Australian populations may be exposed to a broader range of environmental conditions throughout their life cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Concentrations of trace and minor elements in calcified structures of bivalve shells, coral skeletons and foraminiferans provide records of changing water pH (Farmer, Hoenisch, Robinson, & Hill, ; Pelejero & Calvo, ; Spivack, You, & Smith, ), temperature (Corrège, ; Rosenthal, Boyle, & Slowey, ) and water chemistry at the time of biomineralization (Cusack & Freer, ; Ellison, Broome, & Ogilvie, ). The ear bones of bony fish (otoliths) provide analogous calcified structures that are widely used to answer a range of biological and ecological questions on fish movements and habitat use based on their element composition (Brennan et al., ; Elsdon et al., ; Gillanders, Izzo, Doubleday, & Ye, ; Izzo, Doubleday, Grammer, Gilmore, et al, ; Reis‐Santos, Tanner, Vasconcelos, et al., ). Otolith chemistry also provides a means of estimating environmental conditions experienced by individual fish over time (Izzo, Doubleday, Grammer, et al., ; Limburg et al., ; Tanner et al., ; Wheeler, Russell, Fehrenbacher, & Morgan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical threshold between freshwater and estuarine habitats was defined as the mean Ba:Ca ratio measured at the edge of the freshwater otoliths, which was less than one standard deviation (0.18–0.05 = 0.13), as suggested by Mohan et al . () and Fuji et al . () for Sr: Ca .…”
Section: Methodsmentioning
confidence: 87%